Boosting Capacitive Deionization Performance of Commercial Carbon Fibers Cloth via Structural Regulation Based on Catalytic‐Etching Effect. Issue 1 (18th March 2022) - Zhang, Chunjie; Wang, Dong; Wang, Zhen; Zhang, Guangshuai; Liu, Zhichao; Wu, Jie; Hu, Jin; Wen, Guangwu
Abstract : Monolithic carbon electrodes with robust mechanical integrity and porous architecture are highly desired for capacitive deionization but remain challenging. Owing to the excellent mechanical strength and electroconductivity, commercial carbon fibers cloth demonstrates great potential as high‐performance electrodes for ions storage. Despite this, its direct application on capacitive deionization is rarely reported in terms of limited pore structure and natural hydrophobicity. Herein, a powerful metal‐organic framework‐engaged structural regulation strategy is developed to boost the desalination properties of carbon fibers. The obtained porous carbon fibers features hierarchical porous structure and hydrophilic surface providing abundant ions‐accessible sites, and continuous graphitized carbon core ensuring rapid electrons transport. The catalytic‐etching mechanism involving oxidation of Co and subsequent carbonthermal reduction is proposed and highly relies on annealing temperature and holding time. When directly evaluated as a current collector‐free capacitive deionization electrode, the porous carbon fibers demonstrates much superior desalination capability than pristine carbon fibers, and remarkable cyclic stability up to 20 h with negligible degeneration. Particularly, the PCF‐1000 showcases the highest areal salt adsorption capacity of 0.037 mg cm −2 among carbon microfibers. Moreover, monolithic porous carbon fibers‐carbon nanotubes with increased active sites and good structural integrity by in‐situ growth of carbon nanotubes are further fabricated to enhance the desalination performance (0.051 mg cm −2 ). This work demonstrates the great potential of carbon fibers in constructing high‐efficient and robust monolithic electrode for capacitive deionization. Abstract : The porous carbon fibers cloth is developed by a powerful metal‐organic framework‐engaged structural regulation strategy, exhibiting hierarchical pores, superhydrophilicity sheath, and continuous carbon fibers core, demonstrating excellent desalination capacity and electrode regeneration ability.